Government Sponsorship of Muslim and Christian Pilgrim in Nigeria: Socio- Economic and Religious Implication - NGBEA , Terwase Gabriel (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Religious pilgrimages have had great national significance in Nigeria, particularly when seen from the point of view of government involvement in sponsoring Muslim and Christian pilgrimages at the expense of other religions in the country. The Nigerian government at all levels expends billions of naira each year to send exclusively adherents of Islam and Christianity to Mecca and Jerusalem for pilgrimages. While Nigerians continue to live in abject poverty with no basic amenities, the Nigerian government and its citizens continue to sink money in foreign "Holy land." The money used by the Nigerian government to sponsor Muslim and Christian pilgrims to holy land can be channelled to provide basic needs and provide employment opportunities for unemployed Nigerian youth. This paper x-rays the socio-economic and religious implications of government sponsorship of Muslim and Christian pilgrimages with tax payers’ money with the aim of calling an end to these leisure trips of a selected few. The paper, among others, recommends that faith is personal and should be treated as such by political authorities. The privatisation of matters relating to religious pilgrimage will have positive implications for the anti-corruption war and promote peace, harmony, and development. The methodology adopted is historical and phenomenological, using several methods of data collection and analysis done qualitatively.